State of the Art Technologies to Broadcast Epidemic Awareness using Web Crawling - Dhanalakshmi, R; Suprajah, S; Swetha, S; Vaishnavi Kanna, S (International Journal of Computer Sciences and Engineering, 2025)
The main aim is to survey all the necessary papers that helps in building a system that spreads awareness among the people during an epidemic to reduce its severity by giving them general information regarding the epidemic diseases and predictions about its severity. There is no proper information among the public regarding the symptoms, precautions and treatment information of any epidemic disease during its spread which leads to unnecessary panic among the public. An android application specially tailored to provide prompt information to the public during the spread of an epidemic disease will be an efficient solution to diminish its spread. This application uses state of the art technology like firebase cloud messaging, firestore, python web scraper and parsehub to accomplish its goal. Thus, the proposed system has all the necessary features to create appropriate awareness among the public during the spread of any epidemic thereby reducing unwanted panic leading to reduction in the severity of the disease.